2011
DOI: 10.1364/oe.19.002852
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of field-free molecular alignment by spatial (de)focusing effects

Abstract: We directly measure the field-free molecular alignment of various room-temperature molecular gases based on alignment-induced spatial focusing and defocusing effects. By imaging the spatial profile of a time-delayed probe pulse with increased and decreased local intensity at the beam center, the parallel and perpendicular molecular alignments are clearly characterized. Meanwhile, the electronic Kerr effect, weak plasma contribution and field-free molecular alignment impact could be distinguished from the measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Our result indicated that either Kerr or molecular alignment could be utilized to characterize unknown laser pulses, while the molecular alignment was the dominative one for molecular gas and showed a very high signal-to-noise ratio. Moreover, the dissimilarity between such two phenomena and their independent contributions to the gate function were clarified by simply comparing the measured FROG traces and retrieved gates, which were consistent with the molecular alignment induced spatial (de)focusing measurements [12].…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Our result indicated that either Kerr or molecular alignment could be utilized to characterize unknown laser pulses, while the molecular alignment was the dominative one for molecular gas and showed a very high signal-to-noise ratio. Moreover, the dissimilarity between such two phenomena and their independent contributions to the gate function were clarified by simply comparing the measured FROG traces and retrieved gates, which were consistent with the molecular alignment induced spatial (de)focusing measurements [12].…”
supporting
confidence: 56%
“…Our result indicated that either Kerr or molecular alignment could be utilized to characterize unknown laser pulses, while the molecular alignment was the dominative one for molecular gas and showed a very high signal-to-noise ratio. Moreover, the dissimilarity between such two phenomena and their independent contributions to the gate function were clarified by simply comparing the measured FROG traces and retrieved gates, which were consistent with the molecular alignment induced spatial (de)focusing measurements [12].The experiment was performed with a Ti:sapphire laser system delivering 50 fs laser pulse at 800 nm, which was split into an excitation and a probe pulse. The excitation pulse was used to generate Kerr effect or align molecules, while the probe passed through a β barium borate (BBO) crystal (type I, 29.2 deg cut, 100 μm thick) to produce a frequency-doubled 400 nm target pulse.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…This has sparked intriguing applications in high-order harmonic generation control [7,8], full-dimensional molecular manipulation [9], and molecular-orbital reconstruction [10]. Molecular alignment was also demonstrated to induce spatiotemporal phase modulation [11], which provides additional degrees of freedom to control ultrashort pulse compression [12], central wavelength tuning of few-cycle ultrashort pulses [13], spatial (de)focusing and regularization [14], as well as filament propagation and interactions [15]. Interestingly, different molecular structures or properties exhibit different alignment characteristics and these differences exactly reveal the rotational dynamics after the impulsive pre-excitation, facilitating some methods to retrieve polarizability anisotropies and other intrinsic molecular parameters requisite for molecular chemistry and physics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental explorations on the interaction of multiple femtosecond filaments have already revealed quite a lot intriguing features of spatiotemporal light bullets with abundant self-action and cross-coupling nonlinearities [13][14][15][16][17]. In molecular gases, the spatiotemporal phase modulation induced by molecular alignment [18,19] offers an additional degree of freedom to control filamentation [20][21][22][23][24][25] and filament interaction [26,27]. Nonlinear filament interaction and its dynamic control may not only stimulate potential applications with nonlinearly coupled multiple filaments instead of single filaments but also solve current challenge on coalescence of multiple intense ultrashort pulses to beat the tightly guided peak intensity beyond the intensity-clamping limit.…”
Section: Introductionmentioning
confidence: 99%